2019
DOI: 10.1093/mnras/stz1974
|View full text |Cite
|
Sign up to set email alerts
|

Possible origin of the slow-diffusion region around Geminga

Abstract: Geminga pulsar is surrounded by a multi-TeV γ-ray halo radiated by the high energy electrons and positrons accelerated by the central pulsar wind nebula (PWN). The angular profile of the γ-ray emission reported by HAWC indicates an anomalously slow diffusion for the cosmic-ray electrons and positrons in the halo region around Geminga. In the paper we study the possible mechanism for the origin of the slow diffusion. At first, we consider the self-generated Alfvén waves due to the streaming instability of the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 46 publications
(60 reference statements)
7
59
0
Order By: Relevance
“…Residing inside the parent SNR may not be the unique picture for the preexisting-type interpretation. It is also possible that Geminga is now running into the stellar-wind bubble that creates the Gemini Hα Ring [16]. The stellar wind from the several OB type stars can provide adequate and continuous energy for the turbulence generation.…”
Section: Resultsmentioning
confidence: 99%
“…Residing inside the parent SNR may not be the unique picture for the preexisting-type interpretation. It is also possible that Geminga is now running into the stellar-wind bubble that creates the Gemini Hα Ring [16]. The stellar wind from the several OB type stars can provide adequate and continuous energy for the turbulence generation.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the extension is too small to be produced by particles that propagate in the standard Galactic diffusion coefficient, since the expected size would be a factor of ∼100 larger in that case. A possible explanation has been searched for in a modification of the diffusion properties around that source, possibly conveyed by self-generated turbulence associated with electrons and positrons leaking the nebula [146], or due to the injection of MHD turbulence by the parent SNR [147]. At present, understanding the formation of TeV halos is one of the big challenges in high-energy astrophysics (see e.g., Lopez-Coto et al in preparation), both for their possible implications for galactic cosmic ray transport and for their implications for future gamma-ray observations.…”
Section: The Crab Nebula and The Other Pwnementioning
confidence: 99%
“…This may be explained by some CR self-confinement effect, leading to suppression of the diffusion coefficient due to increased magnetic turbulence in the immediate vicinity of the accelerator, which several studies have shown for pulsar environments [83], and [82] demonstrated that a similar effect is seen in SNRs. Alternative explanations have also been sought, such as turbulence of the surrounding medium generated by the shock wave of the parent SNR [84]. [85] presented a study investigating whether a ballistic (of the gyro-centre) component to the particle transport description may alleviate the requirement of a slow diffusion coefficient, finding that a more typical value of (1GeV) ∼ 10 28 cm −2 s −1 can be kept, although a highly efficient conversion of the pulsar spin-down energy into leptons is required in this case (∼ 60% compared to 0.3 − 3% for Geminga).…”
Section: Pos(icrc2021)046mentioning
confidence: 99%